Profitability, solvency and stock return property industry in Indonesia - Zamzany, Faizal Ridwan; Setiawan, Edi; Muhsarofah, Muhsarofah (JURNAL MANAJEMEN MOTIVASI, 2018)
The purpose of this research is to analyze and determine whether there is a direct effect of Return On Asset (X1) and the Debt to Equity Ratio (X2) the Stock Return (Y) (study on property sector listed in the Indonesian Stock Exchange). The population in this research is 41 companies; samples are seven companies with purposive sampling method. This type of research is quantitative. Analysis of data uses path analysis with SPSS 23. Based on data analysis, the results of this research indicate that the return on asset (X1) decisions positively affect the stock return, while debt to equity ratio (X2) did not significantly affect the stock return.